Low level counting from meteorites to neutrinos - Heusser, Gerd (AIP conference proceedings, 2005)
The development in low level counting at Heidelberg with NaI(Tl) crystals, proportional counters and Germanium detectors is reviewed throughout the course of almost 40 years of experience. Research subjects changed from cosmogenic radionuclides in meteorites to solar neutrinos and double beta decay. Driven by screening measurements for these rare event experiments, the sensitivity in single gamma counting has gained almost 3 orders of magnitude. With Ge spectrometry the muBq/kg range is now accessible. It is discussed how further improvements can be realized. There is potential to reach a sensitivity at the level of 10 to 100 nBq/kg for cryogenic liquid type Gespectroscopy, a technique which the next generation 76Ge double beta decay experiment GERDA is based on.